NILAI-NILAI PENDIDIKAN MORAL DALAM BUKU CATATAN MOTIVASI SEORANG SANTRI (KARYA HABIBURRAHMAN EL-SHIRAZY) - Adyatama, Muhammad Fajar (UIN Antasari Banjarmasin, 2022)
ABSTRACT Today, the value of moral degradation reflected in a child's attitude we often see increasingly denying moral existence itself. In a sense, a child's attitude in a period of education is often not based on anything that a child should have in a period of education. This is in stark contrast with moral and moral education. Masrukhi says that habiburrahman in Catatan Motivasi Seorang Santri’s book seems to want to actually do what is called